2022
DOI: 10.35842/jkry.v9i2.646
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Progressive Relaxation Therapy on Elderly With Insomnia

Abstract: Along with many physiologic changes seen with aging, significant changes also happen in sleep and circadian rhythm across the lifes. Insomnia is a form of sleep disorder that is often experienced by the elderly. Insomnia is difficulty initiating or maintaining sleep. Treatment for insomnia usually begins with the elimination of habits (moving beds, using the bed only to sleep and others) if it doesn't work, it can be treated with hypnotic drugs. In fact, the elderly with all the functional decline of their bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…Journal Homepage: https://jurnal.agdosi.com/index.php/IJHS/index Volume 2 | Number 1 | March 2024 |this method demonstrated that PMR is beneficial in lowering the incidence of insomnia in elderly(Sutrisno, Herawati and Aryani, 2022),(Arianti and Novera, 2019),(Fari, Pranata and Sukistini, 2021). In the same vein, with regard to three additional articles that investigated cognitive behavioral therapy (CBT), two journals utilized systematic methods and literature reviews, as well as application-based CBT(Lee et al, 2024) dan(Mijnster et al, 2022), Additionally, one journal utilized the literature review method(McLaren et al, 2023) and one journal utilized the literature review method (McLaren et al, 2023) without application.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Journal Homepage: https://jurnal.agdosi.com/index.php/IJHS/index Volume 2 | Number 1 | March 2024 |this method demonstrated that PMR is beneficial in lowering the incidence of insomnia in elderly(Sutrisno, Herawati and Aryani, 2022),(Arianti and Novera, 2019),(Fari, Pranata and Sukistini, 2021). In the same vein, with regard to three additional articles that investigated cognitive behavioral therapy (CBT), two journals utilized systematic methods and literature reviews, as well as application-based CBT(Lee et al, 2024) dan(Mijnster et al, 2022), Additionally, one journal utilized the literature review method(McLaren et al, 2023) and one journal utilized the literature review method (McLaren et al, 2023) without application.…”
mentioning
confidence: 89%
“…CBT-I, especially the parts of therapy that concentrate on boosting homeostatic sleep drive, has been demonstrated to alleviate insomnia in the aged and should be utilized to counteract the consequences of aging on sleep.Insomnia following treatment with progressive relaxation. The findings of the research(Sutrisno, Herawati and Aryani, 2022) indicated that patients who received progressive relaxation therapy experienced a reduction in the amount of sleeplessness they experienced. Prior to the implementation of the progressive relaxation therapy, there were seventeen (76.6%) respondents.…”
mentioning
confidence: 96%
“…Six studies were from Indonesia (Lufianti et al, 2023) (Royani & Siska, 2023 (Satria et al, 2023) (Sutrisno et al, 2022) (Nazari et al, 2022) (Muhaningsyah et al, 2021. Turkey 1 research study (Gökşin & Aşiret, 2021), China 1 research study (Li et al, 2020), Egyptian 1 Research (Elsalam & Kholy, 2020).…”
Section: Preexperimentsmentioning
confidence: 99%